Attitudes of the locals towards tourism impact on Palić - Milošević Srđan; Perić Dušan; Vujinović Miljana (University Educons, Faculty of Sports and Tourism, Novi Sad, 2020)
This paper discusses the attitudes of the local population towards the impact of tourism on the tourist destination Palić. By researching the role and the importance of the local population in the process of tourism development, what is presented is the current situation, positive and negative influences as well as the possibilities of improving tourism. The aim of this paper is to determine the impact of tourism on destination Palić observed through the attitudes, involvement, and the contribution of the local population. A sample of 100 adults was surveyed with 18 questions taken from previous similar surveys. The good internal reliability of the questionnaire was determined by using Cronbach's alpha. It was found that the local population of Palić generally highly evaluates the impact of tourism and recognizes its positive impact on the local development. Women were stricter in assessing the impact of tourism, while the assessment of respondents of different ages did not differ significantly. The importance of tourism for the local development is more recognized by those who are engaged in it. However, the real impact of all three factors (gender, age, and engagement in tourism) was small.